2^2x-1=8^x-3

Simple and best practice solution for 2^2x-1=8^x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2^2x-1=8^x-3 equation:



2^2x-1=8^x-3
We move all terms to the left:
2^2x-1-(8^x-3)=0
We get rid of parentheses
2^2x-8^x+3-1=0
We add all the numbers together, and all the variables
2^2x-8^x+2=0
We move all terms containing x to the left, all other terms to the right
2^2x-8^x=-2

You can always share this solution

See similar equations:

| 10=n+8;n=2 | | -(4-w)+2(w-7)=-30 | | r+1.22=2.01 | | 7÷p-4=-8 | | Y3-y2-21y+45=0 | | -12-3n=-18 | | -3-6n=-15 | | 3/4p+6=12 | | r^2-50r+200=0 | | Y2-y-12=0 | | -3-6n=15 | | 7-3n=21 | | 30x-13x=17 | | 3n+2+5n-7=11 | | 19x+(-13x)+(-x)-11x-(-9x)=-9 | | 105+(5x?70)=180 | | 19x-(-13x)+(-x)-11x-(-9x)=-9 | | 19x-18x-x+3x=18 | | 7/2×-5/3=-5/6x-4/5 | | 9x+x+2x-x-7x+2=14 | | 3-6n=15 | | 6x-6x+x+2x=12 | | 12x-5x-7x+x=12 | | (-12x)+9x+(-17x)+(-5x)-(-7x)=18 | | 4.6a=-13.34 | | (-7x)-(-9x)+(-5x)+13x=20 | | 15x+x-5x+4x-5x+2=12 | | -15x-(-17x)+(-3x)+(-18)=1 | | -9x+17x-(-16)=-16 | | 11x+4x-12x-3=12 | | X+3x-2x+x+4x=7 | | 6x-11x+3x-(-7x)=-15 |

Equations solver categories